Mechanochemical carbonated slag, method for production thereof and use thereof
The slag produced by mechanochemical carbonation method and filler used in cement binders solve the problems of low energy efficiency and difficult automation implementation in the prior art, and achieve the effect of efficiently reducing CO2 emissions in cement production and improving concrete performance.
Patent Information
- Application Number
- CN202380067023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-17
- Filing Date
- 2023-08-16
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art When producing fillers for cement adhesives, energy efficiency is low and automation is difficult, and CO2 emissions from cement production cannot be effectively reduced.
The slag is produced by mechanical chemical carbonation method. By mixing the slag precursor with CO2 gas in a mechanical stirring unit for mechanical stirring, a mechanochemical carbonated slag with high specific surface area and amorphous content is generated.
The compressive strength and strength activity index of concrete are improved, water demand and CO2 emissions are reduced, and the production process is efficient in energy and automation is relatively simple.
Smart Images

Figure BDA0005317178140000281 
Figure BDA0005317178140000291 
Figure BDA0005317178140000292
Abstract
Description
Technical Field
[0001] The present invention relates to a mechanochemically carbonated slag. The present invention further relates to a method for its production and its use. The present invention further relates to a composition comprising the mechanochemically carbonated slag and an additional material selected from the group consisting of asphalt, cement, geopolymers, polymers and combinations thereof. The present invention further relates to concrete and a method for its preparation. Background Art
[0002] Concrete is a composite material comprising a matrix of aggregate (typically rock material) and a binder (typically Portland cement or asphalt) that holds the matrix together. Concrete is one of the most commonly used building materials and is said to be the second most widely used material on earth after water.
[0003] In order to reduce the cost of concrete and the CO2 emissions generated by global cement production, a great deal of research effort has been devoted to identifying inexpensive materials that can be used as fillers or alternative binders to replace the binder component without (detrimentally) affecting the properties of concrete. Such secondary cementitious materials are an area of wide industrial interest.
[0004] An example of a widely used cementitious filler is limestone. A comprehensive overview of fillers in cementitious materials can be found in John, Vanderley M., et al. "Fillers in cementitious materials—Experience, recent advances and future potential." Cement and Concrete Research 114 (2018): 65-78.
[0005] The production of Portland cement constitutes about 8% of the world's CO2 emissions. According to Vanderley et al., traditional mitigation strategies for CO2 emissions in the cement industry are insufficient to ensure the necessary mitigation in the face of increasing cement demand. Currently, cement production is increasing due to a combination of increasing urbanization and replacement of old infrastructure. Therefore, the adoption of expensive and environmentally risky carbon capture and storage (CCS) has been recognized by cement industry leaders as an inevitable solution.
[0006] Therefore, there remains a need to develop affordable filler technologies that can combine both the CO2 emission reductions achieved through reduced cement production and the CO2 emission reductions achieved through carbon capture technologies and that do not adversely affect the properties of concrete.
[0007] US 8,709,151 B2 describes a method for producing products by compacting granulated ground blast furnace slag, which is then sent to an autoclave for carbonation under conditions that make water in liquid form. Since US 8,709,151 B2 relies on an autoclave reactor for carbonation, where high temperatures and pressures up to 14 MPa are used, it is not very energy efficient. In addition, since multiple unit operations (including compaction and carbonation) all occur as separate steps, actual implementation and in particular automation are not straightforward.
[0008] It is an object of the present invention to provide an improved filler for geopolymers, cement or bituminous binders.
[0009] A further object of the present invention is to provide improved fillers for geopolymers, cement or bituminous binders which are inexpensive to produce.
[0010] It is a further object of the present invention to provide improved fillers for geopolymers, cement or asphalt binders, which fillers are produced using CO2 capture technology.
[0011] It is a further object of the present invention to provide improved fillers for geopolymers, cement or bituminous binders which improve the properties of the resulting concrete, such as compressive strength, strength activity index and / or water demand. Summary of the invention
[0012] In a first aspect, the present invention provides a mechanochemically carbonated slag, which preferably has a carbonation temperature of 0.1-50 m 2 / g, preferably 0.5-50m 2 The mechanochemically carbonated slag preferably has a D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm and / or an amorphous content of at least 35 wt.%, preferably at least 50 wt.%, preferably at least 60 wt.%, more preferably at least 65 wt.% as determined by XRD.
[0013] Satoshi Asaoka et al.: "Removal of hydrogen sulfide using carbonated steel slag" CHEMICAL ENGINEERING JOURNAL, Vol. 228, March 24, 2013, pp. 843-849 discloses passively carbonated steel slag having a particle size of 0.8-5 mm. As shown in the accompanying examples, the mechanochemically carbonated slag of the present invention has an unexpectedly reduced water demand.
[0014] In another aspect, the present invention provides a method for producing mechanochemically carbonated slag, the method comprising the steps of: a) providing a raw material comprising or consisting of a slag precursor; b) providing a gas comprising CO2, preferably comprising at least 0.5% by volume CO2; c) introducing the raw material and the gas into a mechanical stirring unit; and d) subjecting the feedstock material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit.
[0015] The raw material is preferably solid, so that the present invention provides a method for producing mechanochemically carbonated slag, the method comprising the steps of: a) providing a solid raw material comprising or consisting of a slag precursor; b) providing a gas comprising CO2, preferably comprising at least 0.5% by volume CO2; c) introducing the solid feedstock and the gas into a mechanical stirring unit; and d) subjecting the material of the solid feedstock to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit to obtain a mechanochemically carbonated slag.
[0016] The method can be applied to various types of slag precursors, advantageously producing a unique mechanochemically carbonated slag.
[0017] In another aspect, the present invention provides a mechanochemically carbonated slag obtainable by the method for producing mechanochemically carbonated slag as described herein.
[0018] As will be shown in the attached examples, it was found that when such mechanochemically carbonated slag as described herein is used as a filler in cement, the compressive strength of the resulting concrete unexpectedly increases beyond the value obtained for non-carbonated slag. In particular, the curing time for strength development is strongly improved (shortened) compared to when non-mechanically carbonated slag is used as a filler. In addition, much higher amounts of this mechanochemically carbonated slag can be used as a filler while also producing acceptable or even improved concrete properties.
[0019] It was also found that the durability of concrete produced using the mechanochemically carbonated slag was greatly increased. Without wishing to be bound by any theory, the present inventors believe that this is due to enhanced micro- and sub-micro-scale hydration, reduced chloride permeability, reduced concrete porosity and / or passivation of free lime. Furthermore, the increased oxygen content may lead to better dispersion in polar solvents and better compatibility with materials having epoxy or carboxyl functional groups compared to untreated precursors or raw materials.
[0020] In addition, as shown in the attached examples, compared with pure cement and with the cement filled with non-carbonated slag, water demand is reduced. In view of the reduction in the particle size of mechanochemical carbonation slag compared with non-carbonated slag, this is particularly unexpected. Reduced particle size is usually associated with increased water demand. As compared with untreated raw materials or pure cement, the reduced water demand can contribute to improved characteristics, such as workability, compressive strength, permeability, water tightness, durability, weather resistance, drying shrinkage and the possibility of cracking. For these reasons, the amount of water in the limit and control concrete is important for both workability and service life. Therefore, the present invention allows better control of water demand. The inventors of the present invention have found that the mechanochemical carbonation of the present invention realizes the increase of the overall amorphous content of slag precursor. Without wishing to be bound by any theory, it is believed that when analyzed by XRD, the mechanochemical method of the present invention can cause the increase of amorphous content, wherein at least some crystalline domains that can be present in the raw material are maintained in the form of microcrystallinity via internal structure, and the form of this microcrystallinity persists in a more general disordered structure. Thus, the disordered macrostructure promotes higher reactivity and improves cement hydration.
[0021] Furthermore, the production of mechanochemically carbonated slag relies on an inexpensive CO2 capture technology platform capable of operating on dilute CO2 streams, such as point source emissions directly to combustion equipment, providing a filler that can be produced in an economically viable manner and that combines both the CO2 emission reductions achieved through reduced cement production and the CO2 emission reductions achieved through CO2 sequestration. Thus, the mechanochemically carbonated slag of the present invention, and in particular the mechanochemically carbonated slag of the present invention, constitutes an excellent filler for many applications, combining different mechanical properties with cost-effective CO2 capture technology.
[0022] In another aspect, the present invention provides a composition comprising the mechanochemically carbonated slag as described herein and an additional material selected from the group consisting of asphalt, cement, geopolymers, polymers, and combinations thereof.
[0023] In another aspect, the present invention provides a method for preparing a composition as described herein, comprising the steps of: (i) providing a mechanochemically carbonated slag as described herein; (ii) providing an additional material selected from the group consisting of asphalt, cement, polymer, geopolymer, and combinations thereof; and (iii) combining the mechanochemically carbonated slag of step (i) with the material of step (ii).
[0024] In another aspect, the present invention provides a method for preparing concrete or mortar, the method comprising the steps of: (i) providing mechanochemically carbonated slag as described herein and an additional material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, optionally in the form of a composition as described herein, wherein the additional material is selected from the group consisting of asphalt, cement, geopolymers and combinations thereof; (ii) supply of construction aggregates; and (iii) contacting, preferably mixing, the mechanochemically carbonated slag of step (i) and the further material with the building aggregate of step (ii) and optionally water.
[0025] In another aspect, the present invention provides a concrete obtainable by the method for preparing concrete as described herein.
[0026] In another aspect, the present invention provides the use of the mechanochemically carbonated slag as described herein: as a filler, preferably as a filler in a material selected from the group consisting of bitumen, geopolymers, cement, mortar, polymers and combinations thereof; As a partial replacement for asphalt, geopolymer or cement in concrete or mortar; Increase the compressive strength of concrete or mortar; Improve the durability of concrete or mortar; Reduce the expansion of concrete Improve the durability of concrete or mortar by reducing chloride permeability and / or porosity; Improve the strength activity index of concrete or mortar; and / or Reduce the water demand of concrete or mortar, Preferably, · Simultaneously improve the strength activity index of concrete and reduce the water demand of concrete; or · Simultaneously improve the strength activity index of the mortar and reduce the water demand of the mortar. DETAILED DESCRIPTION
[0027] As used herein, the expression "comprise" and variations thereof, such as "comprises" and "comprising", should be interpreted in an open, inclusive sense, meaning that the described embodiments include the recited features, but it does not exclude the presence of other features as long as they do not render the embodiment inoperable.
[0028] As used herein, the expressions "one embodiment," "specific embodiment," "embodiment," etc. should be interpreted as meaning that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment. Therefore, the appearance of such expressions in various places throughout this specification does not necessarily refer to the same embodiment. In addition, in one or more embodiments, the particular features, structures, or characteristics may be combined in any suitable manner. For example, certain features of the present disclosure described herein in the context of separate embodiments are also expressly contemplated in combination in a single embodiment.
[0029] Unless the context clearly dictates otherwise, as used herein, the singular forms "a / an" and "the" should be construed to include plural referents. It should also be noted that the term "or" is generally employed in its broadest sense, i.e., meaning "and / or", unless the context clearly dictates otherwise.
[0030] Whenever throughout this document a compound is mentioned as a salt, this should be interpreted as including the anhydrous form of the compound as well as any solvates (especially hydrates).
[0031] The terms "slag precursor" and "slag" as used herein should be interpreted as including any welding or slag, in particular slag from metal production or processing. In a preferred embodiment of the present invention, the slag precursor is blast furnace (BF) slag, air cooled blast furnace (ACBF) slag, granulated blast furnace (GBF) slag, basic oxygen furnace (BOF) slag, ladle furnace basic slag (LS) or electric arc furnace (EAF) slag. The slag precursor is preferably blast furnace (BF) slag, air cooled blast furnace (ACBF) slag, granulated blast furnace (GBF) slag, basic oxygen furnace (BOF) slag, ladle furnace basic slag (LS) or electric arc furnace (EAF) slag from ferrous metal production, non-ferrous metal production, or phosphorus production. The slag precursor is more preferably blast furnace (BF) slag, air cooled blast furnace (ACBF) slag, granulated blast furnace (GBF) slag, basic oxygen furnace (BOF) slag, ladle furnace basic slag (LS) or electric arc furnace (EAF) slag from iron or steel production. The slag precursor is most preferably granulated blast furnace slag which has been optionally ground from iron or steel production.
[0032] The term "mechanochemically carbonated slag" is used herein to refer to the slag obtainable by the mechanochemical carbonation process of the present invention.
[0033] According to the present invention, the BET surface area as referred to herein is determined at a temperature of 77 K using a sample mass of 0.1-0.5 g. The BET surface area as referred to herein is determined using nitrogen. A preferred analytical method for determining the BET surface area comprises heating the sample to 400° C. for a desorption cycle prior to the surface area analysis. A suitable and therefore preferred analytical device for determining the BET surface area is a Micromeritics Gemini VII 2390 surface analyzer preferably equipped with a Micromeritics FlowPrep 060 flow gas degassing unit.
[0034] As used herein, TGA refers to thermogravimetric analysis, a technique known to those skilled in the art. A preferred TGA setting for determining the CO content of raw materials and carbonating materials in the context of the present invention is a Setaram TAG 16TGA / DSC dual chamber balance, using a 0.1-2 mg sample. According to the present invention, TGA is carried out under an inert atmosphere such as nitrogen or argon.
[0035] According to the present invention, the particle size distribution characteristics such as D10, D50 and D90 and specific surface area (unless explicitly mentioned as BET surface area) mentioned herein are measured using the Fraunhofer theory of light scattering with a laser scattering particle size analyzer (such as Brookhaven laser particle size analyzer, model Microbrook 2000LD or other instruments with equal or better sensitivity) and the data are reported using the volume equivalent sphere model. As known to the skilled person, D50 is the mass median diameter, that is, the diameter at which 50% of the sample mass is composed of smaller particles. Similarly, D10 and D90 represent the diameter at which 10% or 90% of the sample mass is composed of smaller particles.
[0036] According to the present invention, the compressive strength, strength-activity index and water demand as mentioned herein are determined according to ASTM C311 / C311M-22. As will be apparent to the skilled person, when performing these tests, the slag precursor or carbonated slag of the present invention is used instead of the "fly ash or natural pozzolan" specified by the standard.
[0037] According to the present invention, the X-ray diffraction (XRD) determinations referred to herein are performed using corundum standards. A suitable and therefore preferred XRD analysis setup is by using a PANalytical Aeris X-ray diffractometer, wherein Rietveld refinement is performed (e.g. using HighScore Plus XRD analysis software).
[0038] For purposes of this disclosure, the ideal gas law is assumed such that volume % of a gas is considered equal to mol %. Mechanochemical Carbonation of Slag
[0039] Therefore, in a first aspect, the present invention provides a mechanochemically carbonated slag, which preferably has a carbonation temperature in the range of 0.1-50 m 2 / g, preferably 0.5-50m 2 / g. Mechanochemically carbonated slag is obtainable by carbonation of a slag precursor. Mechanochemically carbonated slag preferably has a D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm and / or an amorphous content of at least 35 wt.%, preferably at least 50 wt.%, preferably at least 60 wt.%, more preferably at least 65 wt.%, as determined by XRD.
[0040] The mechanochemically carbonated slag preferably has an amorphous content of at least 50 wt.%, preferably at least 60 wt.%, more preferably at least 65 wt.%, as determined by XRD. As shown in the attached examples, the inventors of the present invention have found that the mechanochemically carbonated method herein enables such a high amorphous content slag to be obtained. This is particularly preferred when the slag is obtained from a slag precursor, which is a blast furnace (BF) slag, an air cooled blast furnace (ACBF) slag, a granulated blast furnace (GBF) slag, a basic oxygen furnace (BOF) slag, a ladle furnace basic slag (LS) or an electric arc furnace (EAF) slag, the precursor having an amorphous content of less than 45 wt.%, preferably less than 40 wt.%, as determined by XRD. It is further preferred that the larnite content of the mechanochemically carbonated slag as determined by XRD is less than 20 wt.%, preferably less than 14 wt.%, more preferably less than 10 wt.%. In other embodiments of the present invention, the mechanochemically carbonated slag preferably has an amorphous content of at least 30 wt.%, preferably at least 35 wt.%, more preferably at least 40 wt.%, and most preferably at least 45 wt.%, as determined by XRD.
[0041] In a preferred embodiment of the present invention, the mechanochemically carbonated slag meets the strength requirements set forth in ASTM C618-12a (2012) and CSAA3001-18 (2018).
[0042] In an embodiment of the present invention, the mechanochemically carbonated slag has a thickness of at least 0.1 m 2 / g, preferably at least 0.5m 2 / g specific surface area.
[0043] In a preferred embodiment of the present invention, the mechanochemically carbonated slag has a thickness of less than 50 m 2 / g, preferably less than 30m2 / g, more preferably less than 10m 2 For example, the specific surface area is less than 50 m 2 / g, less than 48m 2 / g, less than 46m 2 / g, less than 44m 2 / g, less than 42m 2 / g, less than 40m 2 / g, less than 38m 2 / g, less than 36m 2 / g, less than 34m 2 / g, less than 32m 2 / g, less than 30m 2 / g, less than 28m 2 / g, less than 26m 2 / g, less than 24m 2 / g, less than 22m 2 / g, less than 20m 2 / g, less than 18m 2 / g, less than 16m 2 / g, less than 14m 2 / g, less than 12m 2 / g, less than 10m 2 / g, less than 8m 2 / g, less than 6m 2 / g and other specific surface areas.
[0044] In a highly preferred embodiment, the mechanochemically carbonated slag has a thickness of less than 5 m 2 / g, preferably less than 3m 2 / g, more preferably less than 2m 2 For example, the mechanochemically carbonated slag may have a specific surface area of less than 5.0 m 2 / g, less than 4.5m 2 / g, less than 4.0m 2 / g, less than 3.5m 2 / g, less than 3.0m 2 / g, less than 2.5m 2 / g, less than 2.0m 2 / g, less than 1.5m 2 / g and other specific surface areas.
[0045] The inventors have observed that mechanochemically carbonated slag having a specific surface area within the ranges specified herein has specific properties when considering performance, processing, etc., compared to untreated precursors or even carbonated materials having other surface areas. Thus, according to a highly preferred embodiment of the present invention, the mechanochemically carbonated slag has a specific surface area of 0.1-50 m2 / g, preferably 0.5-50m 2 / g specific surface area, such as 0.1-50m 2 / g, preferably 0.1-30m 2 / g, more preferably 0.1-10m 2 / g in the range of specific surface area; 0.1-5.0m 2 / g, preferably 0.1-3.0m 2 / g, more preferably 0.1-2.0m 2 / g in the range of specific surface area; 0.5-50m 2 / g, preferably 0.5-30m 2 / g, more preferably 0.5-10m 2 / g in the range of specific surface area; 0.5-5.0m 2 / g, preferably 0.5-3.0m 2 / g, more preferably 0.5-2.0m 2 / g range of specific surface area, etc.
[0046] In an embodiment of the present invention, the mechanochemically carbonated slag has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-5 μm; D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm; • D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm.
[0047] In an embodiment of the present invention, the mechanochemically carbonated slag has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-5 μm; D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm; D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm and having an amorphous content of at least 45 wt. % as determined by XRD.
[0048] In an embodiment of the present invention, the mechanochemically carbonated slag has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-5 μm; D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm; D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm and having an amorphous content of at least 40 wt. % as determined by XRD.
[0049] In an embodiment of the present invention, the mechanochemically carbonated slag has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-5 μm; D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm; D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm and having an amorphous content of at least 35 wt. % as determined by XRD.
[0050] In an embodiment of the present invention, the mechanochemically carbonated slag has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-5 μm; D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm; D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm and has an amorphous content of at least 30 wt. % as determined by XRD.
[0051] In an embodiment of the present invention, there is provided a mechanochemically carbonated slag of the present invention obtainable by simultaneous carbonation and size reduction of a slag precursor, wherein the ratio of D50 of the mechanochemically carbonated slag to the D50 of the slag precursor is less than 0.5:1, preferably less than 0.1:1, and more preferably less than 0.05:1.
[0052] The carbonated slag preferably has a CO2 content of at least 1 wt.%, more preferably at least 1.5 wt.%, most preferably at least 2.2 wt.%, wherein the CO2 content is determined as a mass loss above 450°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min. Preferably, the mechanochemically carbonated slag is obtainable by carbonation of a slag precursor, wherein the ratio of the CO2 content of the mechanochemically carbonated slag to the CO2 content of the slag precursor is at least 1.5:1, preferably at least 2:1, more preferably at least 2.2:1, wherein the CO2 content is determined as a mass loss above 450°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min.
[0053] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in specific surface area achieved by the dry mechanochemical carbonation method of the present invention is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in an embodiment of the present invention, a mechanochemically carbonated slag obtainable by simultaneous carbonation and increase in specific surface area of a slag precursor is provided, wherein the ratio of the specific surface area of the mechanochemically carbonated slag to the specific surface area of the slag precursor is at least 1.2:1, preferably at least 1.4:1, and more preferably at least 1.6:1. The inventors have observed that a ratio of the specific surface areas of at least 1.8 provides even better results.
[0054] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in BET surface area achieved by the dry mechanochemical carbonation method of the present invention is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in an embodiment of the present invention, a mechanochemically carbonated slag obtainable by simultaneous carbonation and BET surface area increase of a slag precursor is provided, wherein the ratio of the specific surface area of the mechanochemically carbonated slag to the BET surface area of the slag precursor is at least 2:1, preferably at least 3:1, and more preferably at least 3.5:1.
[0055] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in amorphous content achieved by the dry mechanochemical carbonation method of the present invention is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in an embodiment of the present invention, a mechanochemically carbonated slag obtainable by simultaneous carbonation of a slag precursor and an increase in amorphous content is provided, wherein the absolute difference between the amorphous content (expressed as % based on total weight) of the mechanochemically carbonated slag and the amorphous content (expressed as % based on total weight) of the slag precursor is at least 20 percentage points, preferably at least 30 percentage points, more preferably at least 35 percentage points. The amorphous content is determined by XRD. In other embodiments of the present invention, the absolute difference between the amorphous content (expressed as % based on total weight) of the mechanochemically carbonated slag and the amorphous content (expressed as % based on total weight) of the slag precursor is at least 5 percentage points, preferably at least 10 percentage points, more preferably at least 15 percentage points, wherein the amorphous content is determined by XRD.
[0056] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in BET surface area achieved by the dry mechanochemical carbonation method of another aspect of the present invention (which is described elsewhere herein) can be largely attributed to the increase in the number of pores observed by the reduction in average pore width and the increase in total pore surface area. Therefore, in an embodiment of the present invention, a mechanochemically carbonated slag obtainable by simultaneous carbonation and BET surface area increase of a slag precursor is provided, wherein the BJH desorption cumulative surface area of the pores of the mechanochemically carbonated slag is at least 110%, preferably at least 120%, and more preferably at least 150% of the BJH desorption cumulative surface area of the pores of the slag precursor, and the desorption average pore width (4V / A obtained by BET) of the mechanochemically carbonated slag is no more than 90%, preferably no more than 85%, and more preferably no more than 80% of the desorption average pore width (4V / A obtained by BET) of the slag precursor.
[0057] In an embodiment of the present invention, the mechanochemically carbonated slag has a strength activity index (SAI) of at least 75%, preferably at least 80% at day 7. The inventors have observed that the mechanochemical process of the present invention allows to obtain a carbonated slag with an excellent SAI at day 7. Therefore, in a highly preferred embodiment, the mechanochemically carbonated slag has a SAI of at least 85%, preferably at least 90%, more preferably at least 95% at day 7.
[0058] In an embodiment of the present invention, the mechanochemically carbonated slag has a strength activity index (SAI) of at least 85%, preferably at least 90% at day 28. The inventors have observed that the mechanochemical process of the present invention allows to obtain a carbonated slag with an excellent SAI at day 28. Therefore, in a highly preferred embodiment, the mechanochemically carbonated slag has a SAI of at least 100% at day 28.
[0059] In an embodiment of the present invention, the mechanochemically carbonated slag has a water demand of less than 97%, preferably less than 96%, more preferably less than 95%. The inventors have observed that the mechanochemical method of the present invention allows to obtain a carbonated slag with an extremely low water demand. Therefore, in a highly preferred embodiment, the mechanochemically carbonated slag has a water demand of less than 94%, preferably less than 93%.
[0060] In an embodiment, the mechanochemically carbonated slag comprises a mixture of silicon dioxide (SiO2) and other metal oxides. The mechanochemically carbonated slag typically contains other metal sulfides and elemental metals. In a preferred embodiment, the mechanochemically carbonated slag is obtainable by carbonation of slag from iron or steel production.
[0061] In an embodiment of the present invention, the mechanochemically carbonated slag comprises: 10 wt.% - 40 wt.% SiO2 (based on the total weight of the mechanochemical carbonation slag); Less than 90 wt.% (based on the total weight of the mechanochemically carbonated slag), preferably less than 80 wt.% (based on the total weight of the mechanochemically carbonated slag), more preferably less than 70 wt.% (based on the total weight of the mechanochemically carbonated slag), even more preferably less than 60 wt.% (based on the total weight of the mechanochemically carbonated slag) of metal oxides other than SiO2.
[0062] In a further embodiment of the invention, the mixture of metal oxides other than SiO2 has one, two, three or all four, preferably all four, of the following characteristics: a total content of calcium oxide and calcium hydroxide in the range of 30 wt.% to 60 wt.% (based on the total weight of the mechanochemically carbonated slag); a total content of iron oxide and iron hydroxide in the range of 1 wt.% to 30 wt.% (based on the total weight of the mechanochemically carbonated slag); a total content of magnesium oxide and magnesium hydroxide in the range of 1 wt.% to 10 wt.% (based on the total weight of the mechanochemically carbonated slag); - A total content of aluminium oxide and aluminium hydroxide in the range of 10 wt.% - 30 wt.% (based on the total weight of the mechanochemically carbonated slag).
[0063] In a preferred embodiment, the mechanochemically carbonated slag contains calcium oxide and calcium hydroxide, magnesium oxide and magnesium hydroxide, SiO2, and aluminum oxide and aluminum hydroxide, and their contents are such that the sum of the total contents of calcium oxide and calcium hydroxide, magnesium oxide and magnesium hydroxide, and SiO2 accounts for at least two-thirds by weight (66.7% by weight) of the weight of the mechanochemically carbonated slag, and the weight ratio of the total content of calcium oxide and calcium hydroxide and magnesium oxide and magnesium hydroxide to the content of silicon dioxide (for example, the ratio of calcium oxide and magnesium oxide to silicon dioxide is expressed as (CaO+MgO) / SiO2) is greater than 1.0. Method for producing mechanochemically carbonated slag and mechanochemically carbonated slag obtainable therefrom
[0064] Without wishing to be bound by any theory, the inventors of the present invention believe that the dry mechanochemical carbonation process of the present invention imparts unique and desirable properties to the carbonated slag obtainable by the process. For example, it is believed that the unique surface area and pore characteristics achieved by the dry mechanochemical carbonation process of the present invention are important to achieving the unexpected performance of the material in, for example, concrete.
[0065] In a further aspect, the present invention provides a method for producing mechanochemically carbonated slag, the method comprising the steps of: a) providing a raw material comprising or consisting of a slag precursor; b) providing a gas comprising CO2, preferably comprising at least 0.5% by volume CO2; c) introducing the solid feedstock and the gas into a mechanical stirring unit; and d) subjecting the material of the solid feedstock to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit to obtain a mechanochemically carbonated slag.
[0066] The raw material is preferably a solid raw material, so that the present invention preferably provides a method for producing mechanochemically carbonated slag, the method comprising the steps of: a) providing a solid raw material comprising or consisting of a slag precursor; b) providing a gas comprising at least 0.5% by volume of CO2; c) introducing the solid feedstock and the gas into a mechanical stirring unit; and d) subjecting the material of the solid feedstock to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit to obtain a mechanochemically carbonated slag. Method Description
[0067] The term "raw material" should be interpreted as a material consisting of or containing a slag precursor. The slag precursor can be mixed with other materials (e.g. fly ash) to form the raw material. The term "precursor" is used to indicate the slag before it is subjected to the mechanochemical carbonation of the present invention. However, preferably, the raw material consists essentially of the slag precursor and optionally water, because this allows the process conditions to be optimized to achieve the desired carbonated slag properties without having to consider the properties of other materials present in the raw material.
[0068] Based on the guidance provided in this disclosure, it is within the capabilities of a person skilled in the art to adapt the relevant process parameters such that a mechanochemically carbonated slag having the properties described herein is obtained.
[0069] The gas provided in step (b) may be any gas stream comprising CO 2 , such as normal air, a waste gas stream having a low CO 2 concentration, or a concentrated CO 2 stream.
[0070] In embodiments of the methods described herein, the gas provided in step (b) is normal air.
[0071] In a highly preferred embodiment of the method described herein, the gas provided in step (b) is a combustion flue gas, particularly a flue gas from fossil fuel combustion, wood pellet combustion, biomass combustion or municipal waste combustion. Fossil fuel combustion can be coal, oil, petroleum coke, natural gas, shale oil, asphalt, tar sand oil or heavy oil combustion or any combination thereof. The combustion flue gas can optionally have been treated to reduce water content, SO2 content, and / or NOx content.
[0072] The CO2 concentration in the gas provided in step (b) is preferably at least 0.1 volume %, more preferably at least 0.5 volume %. Typical CO2 concentrations of combustion flue gases are in the range of 1 volume %-15 volume % (such as 2 volume %-5 volume %), so that it is preferred that the gas provided in step (b) has a CO2 concentration in the range of 1 volume %-10 volume % (such as 2 volume %-5 volume %). In an alternative embodiment of the present invention, the gas provided in step (b) contains at least 80 volume % CO2, preferably at least 95 volume % CO2. In some embodiments of the present invention, the gas provided in step (b) contains at least 80 volume % CO2, preferably at least 95 volume % CO2 and less than 1000 ppm (v / v) of H2O, preferably less than 100 ppm (v / v) of H2O. In some embodiments, the gas provided in step (b) contains at least 0.1 volume % CO2 and H2O in the range of 5 volume %-25 volume %. For example, in the case of flue gas, the gas provided in step (b) preferably contains CO in the range of 1 volume %-15 volume % (such as 2 volume %-10 volume %) and H in the range of 5 volume %-25 volume % (such as 15 volume %-20 volume %) O. The gas is typically not in a supercritical state, because this is not necessary for the mild mechanochemical carbonation method of the present invention. Therefore, in any embodiment of the present invention, it is highly preferred that the gas is not in a supercritical state.
[0073] In some embodiments of the invention, the methods described herein provide that the temperature and pressure during step (d) are such that the pressure is below the saturated vapor pressure of water at the temperature in the mechanically agitated unit.
[0074] In step (d), the expression "in the presence of said gas" should be interpreted as meaning that the atmosphere inside the mechanical stirring unit at the start of step (d) consists essentially of the gas provided in step (b). The skilled person will understand that unless the reactor (mechanical stirring unit) is continuously purged or replenished, the composition of the gas will change as the reaction progresses.
[0075] Typically, step (d) can be carried out at atmospheric pressure, below atmospheric pressure or above atmospheric pressure. Typically, it is preferred that step (d) is carried out at atmospheric pressure or above atmospheric pressure. Therefore, it is preferred that step (d) is carried out at a pressure of at least about 100kPa (e.g., at least 101.325kPa). In a preferred embodiment of the present invention, step (d) is carried out at a pressure greater than about 300kPa (e.g., 303.975kPa), preferably greater than about 600kPa (e.g., 607.95kPa). In an alternative embodiment of the present invention, step (d) is carried out at a pressure less than about 100kPa (e.g., at least 101.325kPa), such as less than 50kPa or less than 10kPa. The technician will understand that (if not actively maintained) the pressure of the gas will change as the reaction progresses. In these embodiments, it should be understood that when step (d) is started, the pressure inside the mechanical stirring unit is as specified herein. In some embodiments, throughout most or substantially all of step (d), the pressure inside the mechanical stirring unit is as specified herein.
[0076] In the highly preferred embodiment of the method described herein, step (d) is carried out under a pressure lower than the critical pressure of carbon dioxide. In addition, the inventors have found that the preparation of the mechanochemical carbonation slag of the present invention does not require very high pressure, so that the method can be carried out in a very energy efficient manner. Therefore, preferably, step (d) is carried out under a pressure less than 10000kPa, preferably less than 5000kPa, more preferably less than 2500kPa and most preferably less than 1000kPa. The technician will understand that the pressure of the gas (if not actively maintained) will change with the progress of the reaction. In these embodiments, it should be understood that at least one time point during step (d), for example, when step (d) is started, the pressure inside the mechanical agitation unit is as specified herein. In certain embodiments, in most of or substantially all of running through step (d), the pressure inside the mechanical agitation unit is as specified herein.
[0077] In a highly preferred embodiment of the method described herein, in order to stimulate carbonation, step (d) is carried out at a temperature of less than 150°C, preferably less than 100°C, preferably less than 90°C, more preferably less than 80°C, and most preferably less than 75°C. In a highly preferred embodiment of the present invention, step (d) is carried out at a temperature in the range of 30°C-85°C (such as 45°C-85°C), preferably 55°C-70°C. In a highly preferred embodiment of the present invention, step (d) is carried out at a temperature of less than 60°C, preferably less than 50°C. As shown in the attached examples, at a temperature below 60°C, a high carbonation efficiency is achieved. Particularly preferred is a temperature in the range of 25°C-60°C, such as 30°C-50°C or 35°C-45°C. In some embodiments, step (d) is carried out at a temperature of less than 40°C, such as less than 35°C or less than 30°C. In a preferred embodiment of the present invention, no active heating is applied, and any increase in temperature is attributed to friction caused by mechanical agitation or to an exothermic reaction occurring during mechanochemical carbonation. The temperature is preferably determined on the solid material in the reactor (ie the mechanically stirred unit) during processing.
[0078] In an embodiment of the invention, step (d) is performed for at least 1 minute, preferably at least 30 minutes, such as at least 1 hour, at least 4 hours, or at least 8 hours.
[0079] In a preferred embodiment of the present invention, step (d) is substantially free of CO2 solubilizers, such as glycerol (propane-1,2,3-triol). Such CO2 solubilizers function to enhance the solubility of carbon dioxide in aqueous solution and allow the formation of carbonic acid concentration for sequestration of carbon dioxide.
[0080] The low temperature requirement of the process of the present invention means that fossil fuels are not required, and electric heating means (or a green fuel source of low calorific value) can realistically be used to supply heat in cases where the friction caused by mechanical stirring is insufficient to reach the desired temperature (such as greater than 45° C.). In this way, fossil fuels can be avoided throughout the entire production chain.
[0081] As with any chemical process, the appropriate reaction time is highly dependent on the desired degree of carbonation, the desired surface area, and the applied pressure, temperature, and mechanochemical agitation, and can be readily determined by periodically sampling the material and monitoring the progress of the reaction, for example via BET analysis, particle size analysis, specific surface area, and CO2 content as explained herein.
[0082] The inventors of the present invention have also found that the mechanochemical carbonation method described herein can be advantageously carried out without the use of additional oxidants such as acids. Therefore, the mechanochemical carbonation method described herein is preferably carried out without the use of strong acids, preferably without the use of any additional oxidants other than the gas provided in step (b).
[0083] In a preferred embodiment of the present invention, the mechanical stirring operation of step (d) comprises grinding, milling, mixing, stirring (such as low-speed stirring or high-speed stirring), shearing (such as high-torque shearing), vibration, blending, pulverizing, powdering, crushing, crushing, fluidized bed or ultrasonic treatment, preferably grinding, milling, mixing, stirring (such as low-speed stirring or high-speed stirring), shearing (such as high-torque shearing) or ultrasonic treatment. The inventors of the present invention have found that if the mechanochemical stirring operation of step (d), the mechanochemical stirring operation of step (d) is carried out in the presence of grinding or milling media, preferably balls or beads, then the mechanochemical carbonation method is promoted. Preferred materials are stainless steel or aluminum oxide. In such highly preferred embodiments, the mechanical stirring operation can be a mechanical stirring unit that simply rotates a solid raw material, a grinding or milling media and a gas. For example, the grinding or milling media can be made of steel (e.g., AISI H13, modified H10), aluminum oxide, chrome white cast iron (e.g., ASTM A532), molybdenum steel (e.g., AISIM2, M4, M-42), chromium-based steel (e.g., H11, H12, H13 CPM V9, ZDP-189), or other media with a target HRC hardness of 60. Such grinding media can be utilized with or without surface treatments such as nitriding and carburizing. This can conveniently be performed in a rotating drum. It should be understood that when performed in a rotating drum, the products obtainable by the method of the present invention can also be obtainable using alternative grinding or milling techniques known to the skilled person.
[0084] In a preferred embodiment of the present invention, step (d) is carried out in the presence of a catalyst, preferably a metal oxide catalyst such as a transition metal oxide catalyst. Examples of suitable catalysts are selected from the group consisting of iron oxide, cobalt oxide, ruthenium oxide, titanium oxide, nickel oxide, aluminum oxide and combinations thereof.
[0085] Thus, as will be appreciated from the above, in a highly preferred embodiment of the invention, step (d) comprises grinding, milling, mixing, stirring (such as low speed stirring or high speed stirring), shearing (such as high torque shearing), shaking, blending, pulverizing, powdering, crushing, breaking, fluidizing bed or ultrasonic treatment, preferably grinding, milling, mixing, stirring (such as low speed stirring or high speed stirring), shearing (such as high torque shearing), or ultrasonic treatment in the presence of grinding or milling media and a metal oxide catalyst.
[0086] The inventors of the present invention have found that, considering the efficiency (such as reaction time, CO2 absorption and particle size reduction) of mechanochemical carbonation, it is advantageous to adopt a medium comprising (such as coated with) the metal oxide catalyst as described herein before and / or adopt a mechanical stirring unit (or part thereof) comprising (or coated with) the metal oxide catalyst, such as on one or more surfaces of contact raw materials during step (d). As explained elsewhere herein, the mechanical stirring operation can be a mechanical stirring unit that simply rotates the raw materials or slag precursors, grinding or milling media, metal oxide catalysts and gases for mechanochemical carbonation. This can be conveniently carried out in a rotating drum.
[0087] As will be clear from this specification, in highly preferred embodiments, step (d) is a substantially dry process. Although some moisture may be present and is beneficial to carbonation efficiency, step (d) is highly preferably not performed on an aqueous solution or slurry. The inventors of the present invention have found that performing step (d) on a solid greatly improves energy efficiency (because water does not have to be removed afterwards) and imparts unique properties to the resulting mechanochemically carbonated slag, resulting in a material that is substantially different from, for example, aqueous carbonated materials. This is also reflected in their different properties, for example when used as filler in concrete. In embodiments of the present invention, the solid raw material preferably has a moisture content of less than 10 wt.% (by total weight of the solid raw material), preferably less than 5 wt.%, more preferably less than 2 wt.%.
[0088] According to a highly preferred embodiment of the present invention, the raw material provided in step (a) is a solid raw material. The solid raw material provided in step (a) is highly preferably less than 30wt.% (by the total weight of the solid raw material), preferably less than 20wt.%, more preferably less than 15wt.% moisture content. Considering the carbonation efficiency, the solid raw material preferably has at least 2wt.% (by the total weight of the solid raw material), preferably at least 5wt.%, more preferably at least 10wt.% moisture content. As shown in the attached examples, the highest carbonation efficiency is achieved at a moisture content of at least 10wt.%. At a moisture content of less than 30wt.% (by the total weight of the solid raw material), the raw material remains and behaves like a solid. In some embodiments of the present invention, the solid raw material can have a moisture content of less than 10wt.% (by the total weight of the solid raw material), less than 5wt.%, or less than 2wt.%. At least one time point during step (d), for example when step (d) is started, the solid raw material preferably has the moisture content specified herein. In some embodiments, throughout most or substantially all of step (d), the moisture content of the feedstock is as specified herein.
[0089] Adjusting the moisture content of the feedstock is within the routine capabilities of the skilled artisan based on the guidance provided herein (eg, by spraying the solid feedstock with an aqueous composition such as water before and / or during step (d)).
[0090] In other embodiments, the raw material provided in step (a) is an aqueous slurry, solution or suspension, such as an aqueous slurry. The aqueous slurry, solution or suspension raw material provided in step (a) can have a water content greater than 50wt.% (by the total weight of the aqueous slurry, solution or suspension raw material), for example greater than 70wt.%. At least one time point during step (d), for example when step (d) is started, the aqueous slurry, solution or suspension raw material preferably has a water content specified herein. In some embodiments, throughout most or substantially all of step (d), the water content of the aqueous slurry, solution or suspension raw material is as specified herein.
[0091] In some embodiments, step (d) is followed by a dehydration step to reduce the water content of the obtained mechanochemically carbonated glassy solid.
[0092] In particular, the inventors of the present invention have found that it is important to carry out step (d) so that In step (d) between , i.e. during the combined carbonation and mechanical agitation, a certain degree of carbonation, size reduction and / or surface area increase is achieved. This results in a material significantly different from, for example, a material that is ground and subsequently carbonated. In order to obtain these effects, it is preferred that the step (a) of the method comprises providing a solid raw material as described earlier herein, and step (d) is carried out on the solid raw material provided in step (a).
[0093] Thus, in a highly preferred embodiment, there is provided a process of the invention wherein carbonation, size reduction and / or surface area increase is achieved during step (d) such that the process has one, two, three, or four, preferably all four of the following characteristics: the ratio of the CO2 content of the mechanochemically carbonated slag obtained in step (d) to the CO2 content of the slag precursor of step (a) is at least 1.5:1, preferably at least 2:1, more preferably at least 2.2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min; The ratio of the D50 of the mechanochemically carbonated slag obtained in step (d) to the D50 of the slag precursor of step (a) is less than 0.9:1, preferably less than 0.75:1, more preferably less than 0.6:1; The ratio of the specific surface area of the mechanochemically carbonated slag obtained in step (d) to the specific surface area of the slag precursor of step (a) is at least 1.2:1, preferably at least 1.4:1, more preferably at least 1.6:1; The absolute difference between the amorphous content (expressed as % based on the total weight) of the mechanochemically carbonated slag and the amorphous content (expressed as % based on the total weight) of the slag precursor is at least 20 percentage points, preferably at least 30 percentage points, more preferably at least 35 percentage points. The amorphous content is determined by XRD.
[0094] The skilled person will appreciate that when the material of step (a) is fed to step (d), this means that the carbonation, size reduction and / or surface area specified above During step (d) accomplish.
[0095] Without wishing to be bound by any theory, the inventors of the present invention believe that the increase in BET surface area achieved by the dry mechanochemical carbonation process is associated with the observed beneficial properties (such as excellent strength activity index and reduced water demand). Therefore, in a highly preferred embodiment of the present invention, a method of the present invention is provided, wherein carbonation and BET surface area increase are achieved during step (d) such that the ratio of the BET surface area of the mechanochemically carbonated slag to the BET surface area of the slag precursor is at least 2:1, preferably at least 3:1, more preferably at least 3.5:1.
[0096] In a particularly preferred embodiment of the method of the present invention, the BJH desorption cumulative surface area of the pores of the mechanochemically carbonated slag obtained in step (d) is at least 110%, preferably at least 120%, and more preferably at least 150% of the BJH desorption cumulative surface area of the pores of the slag precursor, and the desorption average pore width (4V / A obtained by BET) of the mechanochemically carbonated slag obtained in step (d) is no more than 90%, preferably no more than 85%, and more preferably no more than 80% of the desorption average pore width (4V / A obtained by BET) of the slag precursor.
[0097] In an embodiment of the present invention, the method described herein does not include a solid-liquid separation step selected from filtration, decantation and gravity separation (e.g., using a cyclone separator) after step (d), and preferably the method of the present invention does not include any solid-liquid separation step after step (d).
[0098] In embodiments of the invention, the methods described herein do not comprise a size selection step, such as a screening or sieving step, after step (d).
[0099] Characteristics of the slag precursor used in the mechanochemical carbonation process of the present invention
[0100] In a preferred embodiment of the method described herein, the slag precursor is a particulate solid material, such as a powder or granular material. In a preferred embodiment of the present invention, the slag precursor is a BF slag, ACBF slag, GBF slag, BOF slag, LS slag or EAF slag. The slag precursor is preferably a BF slag, ACBF slag, GBF slag, BOF slag, LS slag or EAF slag from ferrous metal production, non-ferrous metal production or phosphorus production. The slag precursor is more preferably a BF slag, ACBF slag, GBF slag, BOF slag or EAF slag from iron or steel production. The slag precursor is most preferably a granulated blast furnace slag or basic oxygen furnace slag optionally ground from iron or steel production.
[0101] In a preferred embodiment of the method described herein, the slag precursor is a slag having a thickness of less than 0.6 m 2 / g, preferably less than 0.5m 2 / g, more preferably less than 0.4m 2 / g of particulate solid material.
[0102] The slag precursor preferably has an amorphous content as determined by XRD of less than 45 wt.%, preferably less than wt. 40%.The clinonotite content of the slag precursor as determined by XRD is preferably greater than 20 wt.%, such as greater than 25 wt.%.
[0103] In an embodiment, the slag precursor comprises a mixture of silicon dioxide and metal oxides other than silicon dioxide.Slag precursors typically contain other compounds such as metal sulfides and elemental metals.
[0104] In a highly preferred embodiment of the invention, the slag precursor has one, two, or three, preferably three, of the following features: D10 in the range of 0.1-50 μm, preferably 0.1-20 μm, most preferably 0.1-10 μm; D50 in the range of 5-200 μm, preferably 10-200 μm, most preferably 10-150 μm; • D90 in the range of 10-1000 μm, preferably 20-750 μm, most preferably 40-500 μm. Preferably, the slag precursor has not been subjected to a compaction process.Thus, in some embodiments, the slag precursor has a porosity greater than 40 vol%, preferably greater than 50 vol%.
[0105] In an embodiment of the present invention, the slag precursor comprises: 10 wt.% - 40 wt.% SiO2 (based on the total weight of the slag precursor); Less than 90 wt.% (based on the total weight of the slag precursor), preferably less than 80 wt.% (based on the total weight of the slag precursor), more preferably less than 70 wt.% (based on the total weight of the slag precursor), even more preferably less than 60 wt.% (based on the total weight of the slag precursor) of metal oxides other than SiO2.
[0106] In further embodiments of the invention, the slag precursor has one, two, three or all four, preferably all four, of the following features: a total content of calcium oxide and calcium hydroxide in the range of 30 wt.% to 60 wt.% (based on the total weight of the slag precursor); a total content of iron oxide and iron hydroxide in the range of 1 wt.% to 30 wt.% (based on the total weight of the slag precursor); a total content of magnesium oxide and magnesium hydroxide in the range of 1 wt.% to 10 wt.% (based on the total weight of the slag precursor); • A total content of aluminum oxide and aluminum hydroxide in the range of 10 wt.% to 30 wt.% (based on the total weight of the slag precursor).
[0107] In a preferred embodiment, the slag precursor contains calcium oxide and hydroxide, magnesium oxide and hydroxide, SiO2, and aluminum oxide and hydroxide in amounts such that the sum of the total contents of calcium oxide and hydroxide, magnesium oxide and hydroxide, and SiO2 accounts for at least two-thirds by weight (66.7% by weight) of the weight of the slag precursor, and the weight ratio of the total content of calcium oxide and hydroxide and magnesium oxide and hydroxide to the content of silicon dioxide (for example, the ratio of calcium oxide and magnesium oxide to silicon dioxide is expressed as (CaO+MgO) / SiO2) is greater than 1.0.
[0108] In a preferred embodiment, the chemical composition of the slag precursor is such that the sum of the total content by weight of calcium oxide and calcium hydroxide, magnesium oxide and magnesium hydroxide, SiO2 and aluminum oxide and aluminum hydroxide is greater than or equal to 80% by weight, more preferably greater than or equal to 90% by weight and even better greater than or equal to 95% by weight, relative to the weight of the slag precursor.
[0109] In some embodiments, the slag precursor comprises less than 39% SiO2 by weight, less than 15% aluminum oxide and aluminum hydroxide by weight, greater than 37% calcium oxide and calcium hydroxide by weight, and less than 13% magnesium oxide and magnesium hydroxide by weight, relative to the weight of the slag precursor.
[0110] In some embodiments, the chemical composition of the slag precursor comprises from 33%-37% by weight SiO2, from 9%-14% by weight aluminum oxide and aluminum hydroxide, from 38%-42% by weight calcium oxide and calcium hydroxide, and from 1%-12% by weight magnesium oxide and magnesium hydroxide, relative to the weight of the slag precursor.
[0111] Without wishing to be bound by any theory, it is believed that the presence of at least some alkaline earth metal oxides or hydroxides promotes carbonation. Thus, according to embodiments or preferred embodiments of the present invention, the slag precursor as described herein has a total amount of alkaline earth metal oxides and hydroxides of at least 0.01 wt.%, preferably at least 0.05 wt.%. Characteristics of the mechanochemically carbonated slag obtained in step (d)
[0112] In a preferred embodiment of the method for producing carbonated slag described herein, the carbonated slag obtained in step (d) has a carbonation temperature in the range of 0.1-50 m 2 / g, preferably 0.5-50m 2 / g of specific surface area, making this particularly preferred. The mechanochemically carbonated slag obtained in step (d) preferably has an amorphous content of at least 50wt.%, preferably at least 60wt.%, and more preferably at least 65wt.%, as determined by XRD. As shown in the attached examples, the inventors of the present invention have found that the mechanochemically carbonated method herein enables such a high amorphous content slag to be obtained. This is particularly preferred when the slag is obtained from a slag precursor, which is a blast furnace (BF) slag, an air-cooled blast furnace (ACBF) slag, a granulated blast furnace (GBF) slag, a basic oxygen furnace (BOF) slag, a ladle furnace basic slag (LS) or an electric arc furnace (EAF) slag, the precursor having an amorphous content of less than 45wt.%, preferably less than 40wt.%, as determined by XRD. It is further preferred that the californite content of the mechanochemically carbonated slag obtained in step (d) as determined by XRD is less than 20 wt.%, preferably less than 14 wt.%, more preferably less than 10 wt.%.
[0113] In a preferred embodiment of the present invention, the carbonated slag obtained in step (d) meets the strength requirements set forth in ASTM C618-12a (2012) and CSAA3001-18 (2018). In a specific embodiment, the method described herein does not include a size selection step, such as a screening or sieving step, after step (d), and the carbonated glassy solid in step (d) meets the strength requirements set forth in ASTM C618-12a (2012) and CSAA3001-18 (2018).
[0114] In an embodiment of the present invention, the mechanochemically carbonated slag obtained in step (d) has a carbonation temperature of at least 0.1 m 2 / g, preferably at least 0.5m 2 / g specific surface area.
[0115] In a preferred embodiment of the present invention, the carbonated slag obtained in step (d) has a carbonation temperature of less than 50 m 2 / g, preferably less than 30m 2 / g, more preferably less than 10m 2 / g specific surface area. For example, less than 50m 2 / g, less than 48m 2 / g, less than 46m 2 / g, less than 44m 2 / g, less than 42m 2 / g, less than 40m 2 / g, less than 38m 2 / g, less than 36m 2 / g, less than 34m 2 / g, less than 32m 2 / g, less than 30m 2 / g, less than 28m 2 / g, less than 26m 2 / g, less than 24m 2 / g, less than 22m 2 / g, less than 20m 2 / g, less than 18m 2 / g, less than 16m 2 / g, less than 14m 2 / g, less than 12m 2 / g, less than 10m 2 / g, less than 8m 2 / g, less than 6m 2 / g and other specific surface areas.
[0116] In a highly preferred embodiment, the carbonated slag obtained in step (d) has a carbonation content of less than 5 m 2 / g, preferably less than 3m 2 / g, more preferably less than 2m 2 For example, the mechanochemically carbonated slag may have a specific surface area of less than 5.0 m 2 / g, less than 4.5m 2 / g, less than 4.0m 2 / g, less than 3.5m 2 / g, less than 3.0m 2 / g, less than 2.5m 2 / g, less than 2.0m2 / g, less than 1.5m 2 / g and other specific surface areas.
[0117] The carbonated slag obtained in step (d) preferably has a CO2 content of at least 1 wt.%, more preferably at least 1.5 wt.%, most preferably at least 2.2 wt.%, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trajectory, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min.
[0118] The inventors have observed that mechanochemically carbonated slags having a specific surface area within a certain range provide unexpected carbonation results when compared to untreated precursors. Therefore, according to a highly preferred embodiment of the present invention, the mechanochemically carbonated slag obtained in step (d) has a specific surface area of 0.1-50 m 2 / g, preferably 0.5-50m 2 / g specific surface area, such as 0.1-50m 2 / g, preferably 0.1-30m 2 / g, more preferably 0.1-10m 2 / g in the range of specific surface area; 0.1-5.0m 2 / g, preferably 0.1-3.0m 2 / g, more preferably 0.1-2.0m 2 / g in the range of specific surface area; 0.5-50m 2 / g, preferably 0.5-30m 2 / g, more preferably 0.5-10m 2 / g in the range of specific surface area; 0.5-5.0m 2 / g, preferably 0.5-3.0m 2 / g, more preferably 0.5-2.0m 2 / g range of specific surface area, etc.
[0119] In an embodiment of the present invention, the carbonated slag obtained in step (d) has one, two, or three, preferably three, of the following characteristics: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-5 μm; D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm; • D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm.
[0120] In an embodiment of the present invention, the mechanochemically carbonated slag obtained in step (d) has a strength activity index (SAI) of at least 75%, preferably at least 80% at day 7. The inventors have observed that the mechanochemical process of the present invention allows to obtain a carbonated slag with an excellent SAI at day 7. Therefore, in a highly preferred embodiment, the mechanochemically carbonated slag has a SAI of at least 85%, preferably at least 90%, more preferably at least 95% at day 7.
[0121] In an embodiment of the present invention, the mechanochemically carbonated slag obtained in step (d) has a strength activity index (SAI) of at least 85%, preferably at least 90% at day 28. Thus, in a highly preferred embodiment, the mechanochemically carbonated slag has a SAI of at least 100% at day 28.
[0122] In an embodiment of the present invention, the mechanochemically carbonated slag obtained in step (d) has a water demand of less than 97%, preferably less than 96%, more preferably less than 95%. The inventors have observed that a mechanochemically carbonated slag with a water demand of less than 94%, preferably less than 93%, provides even better results. Mechanochemically carbonated slag obtainable by the process described herein
[0123] The inventors of the present invention have found that the mechanochemical carbonation described herein imparts unique properties to the resulting mechanochemically carbonated slag, resulting in a material that is substantially different from, for example, aqueous carbonated materials. This is also reflected in their different properties, for example when used as filler in concrete. In particular, the inventors of the present invention have found that it is important to carry out step (d) such that During step (d) , i.e. during the carbonation and mechanical stirring of the combination, a certain degree of carbonation, size reduction and / or surface area increase is achieved. This results in a material significantly different from, for example, a carbonating material in an aqueous environment or even a material that is ground and subsequently carbonated. Therefore, on the other hand, the invention provides obtainable mechanochemical carbonation slag by the method for producing mechanochemical carbonation slag as described herein.
[0124] As the skilled person will appreciate from this disclosure, the mechanochemically carbonated slag of the present invention constitutes an excellent filler material for many applications, combining different mechanical properties with a cost-effective CO2 sequestration method. Compositions containing mechanochemically carbonated slag and methods for preparing the same
[0125] In another aspect, the present invention provides a composition comprising the mechanochemically carbonated slag as described herein and an additional material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, preferably cement, more preferably Portland cement.
[0126] In an embodiment, the additional material is a polymer selected from thermoplastic polymers and thermosetting polymers. In a preferred embodiment, the additional component is a polymer selected from the group consisting of epoxy resins, phenolic resins, polyalkylene terephthalates (preferably polyethylene terephthalate), polyalkylene terephthalate adipates (preferably polybutylene terephthalate adipate), polyisosorbide alkylene terephthalates (preferably polyisosorbide ethylene terephthalate), polyalkylene aromatic polyamides (preferably polyethylene aromatic polyamides), polyacrylonitrile, polyacetal, polyimide, aromatic polyester , polyisoprene (preferably cis-1,4-polyisoprene), polyethylene, polypropylene, polyurethane, polyisocyanurate, polyamide, polyether, polyester, polyhydroxyalkanoate, polylactic acid, polylactic acid-co-glycolic acid, polyvinylidene fluoride, polyvinyl acetate, polyvinyl chloride, polystyrene, polytetrafluoroethylene, acrylonitrile-butadiene-styrene, nitrile rubber, styrene butadiene, ethylene-vinyl acetate, copolymers thereof and combinations thereof, more preferably polyolefins such as polypropylene, polyethylene, copolymers thereof and combinations thereof. The term "polymer" as used herein includes copolymers such as block copolymers.
[0127] In a highly preferred embodiment, the additional material is selected from the group consisting of asphalt, cement, geopolymers, and combinations thereof.
[0128] According to the present invention, cement may be hydraulic or non-hydraulic cement. In a preferred embodiment, cement is a hydraulic cement, such as Portland cement. In a highly preferred embodiment of the present invention, cement is one of the cements defined in EN197-1 (2011), preferably Portland cement as defined in EN197-1 (2011).
[0129] In an embodiment of the present invention, the composition contains greater than 0.1wt.% (based on the total weight of the composition), preferably greater than 1wt.%, more preferably greater than 5wt.% of mechanochemically carbonated slag and / or greater than 0.1wt.% (based on the total weight of the composition), preferably greater than 1wt.%, more preferably greater than 20wt.% of additional materials.
[0130] In an embodiment of the present invention, the composition comprises less than 60wt.% (based on the total weight of the composition), preferably less than 50wt.%, more preferably less than 45wt.% of mechanochemically carbonated slag and / or less than 95wt.% (based on the total weight of the composition), preferably less than 90wt.%, more preferably less than 80wt.% of additional materials.
[0131] In an embodiment of the present invention, a composition is provided wherein the weight:weight ratio of the mechanochemically carbonated slag to the additional material is in the range of 1:9 to 2:1, preferably in the range of 1:8 to 1:1, more preferably in the range of 1:6 to 5:6.
[0132] In an embodiment of the present invention, the composition comprises 5wt.%-70wt.% (based on the total weight of the composition), preferably 10wt.%-60wt.%, more preferably 20wt.%-50wt.% of mechanochemically carbonated slag and 30-95wt.% (based on the total weight of the composition), preferably 40wt.%-90wt.%, preferably 50wt.%-80wt.% of additional materials.
[0133] In an embodiment of the invention, the composition comprises less than 5 wt.% (based on the total weight of the composition), preferably less than 1 wt.%, more preferably less than 0.1 wt.% water. The amount of water can be suitably determined as the mass loss up to 120°C measured by TGA using a temperature trace, wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min.
[0134] In an embodiment of the present invention, the composition consists of mechanochemically carbonated slag and additional materials.
[0135] In another aspect, the present invention provides a method for preparing a composition as described herein, comprising the steps of: (i) providing a mechanochemically carbonated slag as described herein, preferably a mechanochemically carbonated slag as described herein; (ii) providing an additional material selected from the group consisting of asphalt, cement, geopolymers, and combinations thereof; (iii) combining the mechanochemically carbonated slag solids of step (i) with the material of step (ii). Method for preparing concrete or mortar
[0136] In another aspect, the present invention provides a method for preparing concrete or mortar, the method comprising the steps of: (i) providing mechanochemically carbonated slag as described herein and an additional material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, optionally in the form of a composition as described herein, wherein the additional material is selected from the group consisting of asphalt, cement, geopolymers and combinations thereof; (ii) providing construction aggregates; (iii) contacting, preferably mixing, the mechanochemically carbonated slag of step (i) and the further material with the building aggregate of step (ii) and optionally water.
[0137] In another aspect, the present invention provides a concrete or mortar obtainable by the method for preparing concrete as described herein.
[0138] In a preferred embodiment of the present invention, step (iii) further comprises contacting, preferably mixing, the mechanochemically carbonated slag of step (i) and the additional material with the building aggregate and water of step (ii). According to the present invention, the mechanochemically carbonated slag of step (i) and the additional material, the building aggregate and water of step (ii) may be contacted, preferably mixed, substantially simultaneously, or in a stepwise manner, wherein the composition of step (i) is first contacted, preferably mixed, with water and then contacted, preferably mixed, with the building aggregate of step (ii).
[0139] In another aspect, the present invention provides the use of the mechanochemically carbonated slag as described herein: as a filler, preferably as a filler in a material selected from the group consisting of bitumen, geopolymers, cement, mortar, polymers and combinations thereof; As a partial replacement for asphalt, geopolymer or cement in concrete or mortar; Increase the compressive strength of concrete or mortar; Improve the durability of concrete or mortar; Reduce the expansion of concrete; Improve the durability of concrete or mortar by reducing chloride permeability and / or porosity; Improve the strength activity index of concrete or mortar; and / or Reduce the water demand of concrete or mortar, Preferably, · Simultaneously improve the strength activity index of concrete and reduce the water demand of concrete; or · Simultaneously improve the strength activity index of the mortar and reduce the water demand of the mortar. Examples
[0140] Particle size distribution and specific surface area measurements were performed on a Brookhaven laser particle size analyzer, model Microbrook 2000LD, using the Fraunhofer theory of light scattering, and data are reported using the volume equivalent sphere model.
[0141] Compressive strength, strength activity index and water demand are measured according to ASTM C311 / C311M-22. As will be apparent to the skilled person, when carrying out these tests, the slag precursor or carbonated slag of the present invention is used instead of the "fly ash or natural pozzolan" specified by the standard.
[0142] The CO2 content was determined as the mass loss above 450°C as measured by TGA using a temperature trace where the temperature was increased from room temperature to 800°C at a rate of 10°C / min. A Setaram TAG 16 TGA / DSC dual chamber balance was used under an inert nitrogen atmosphere with 0.1-2 mg samples.
[0143] Amorphous content was measured by X-ray diffraction (XRD) using corundum standards. XRD data were collected using a PANalyticalAeris X-ray diffractometer. Qualitative XRD analysis and Rietveld refinement were performed using HighScore Plus XRD analysis software. The weight percentage of the amorphous portion of the sample was determined by external standards. Example 1 Sample A
[0144] Mechanochemically carbonated slag is produced by inserting 10.5 kg of slag precursor (ground granulated blast furnace slag) into a pressure cell with 150 kg of a first grinding medium (ceramic bearings of 25.4 mm size) and 150 kg of a second grinding medium (ceramic bearings of 10 mm size). The cell is pressurized to an initial pressure of 448 kPa with flue gas (CO2: 8% by volume -10% by volume; H2O: 18% by volume -20% by volume; O2: 2% by volume -3% by volume; N2: 67% by volume -72% by volume) and rotated on a roller at 38 RPM for 3 days to obtain mechanochemically carbonated slag. The reaction is initiated at room temperature and no heating or cooling is applied. The ceramic bearings have an Al2O3 content of 92 wt.%, so that they are also used as catalysts. The characteristics of the slag precursor and the mechanochemically carbonated slag obtained are shown in the following table. Sample B
[0145] Mechanochemical carbonation slag is produced by inserting 0.9 kg of slag precursor (basic oxygen furnace slag) of sample B into a pressure chamber with 17.5 kg of grinding media (10 mm size ceramic bearings). The chamber is pressurized to an initial pressure of 414 kPa with flue gas (CO2: 8 volume %-10 volume %; H2O: 18 volume %-20 volume %; O2: 2 volume %-3 volume %; N2: 67 volume %-72 volume %), and rotated on a roller at 40 RPM for 2 days to obtain mechanochemical carbonation slag. The reaction is initiated at room temperature and no heating or cooling is applied. The ceramic bearings have an Al2O3 content of 92 wt.%, so that they are also used as catalysts. The characteristics of the slag precursor and the mechanochemical carbonation slag obtained are shown in the following table.
[0146] As can be observed from the strength activity index (SAI) measurements and water demand measurements, the mechanochemically carbonated slag of the present invention provides unexpectedly reduced water demand and increased strength compared to the uncarbonated counterpart and even compared to the Portland cement control. Example 2
[0147] Sample A as described in Example 1 was examined by X-ray diffraction analysis and the five largest fractions identified are shown in the following table.
[0148] Thus, the mechanochemical carbonation process of the present invention was found to achieve a substantial increase in amorphous content. Without wishing to be bound by any theory, the present inventors believe that this is at least partly responsible for the beneficial reduction in water demand observed. Example 3
[0001] The influence of the moisture content of the solid phase and the humidity of the second carbon-rich gas on the carbonation efficiency of basic oxygen furnace slag (BOF) was studied.BOF was placed in a temperature controlled container under the continuous flow of flue gas (4 volume % CO2, temperature and humidity controlled according to the following table).No stirring was applied.Granularity and moisture content were determined according to the method defined earlier in this paper.CO2 absorption was determined by comparing the CO2 content before and after treatment, wherein CO2 content was determined as the mass loss higher than 200°C measured by TGA using temperature trajectory, wherein temperature was increased from room temperature to 800°C at a rate of 10°C / min and then reduced to room temperature at a rate of 10°C / min. All parameters not described were kept constant.
[0002] Similar tests were performed in which the flue gas had a temperature of 60°C and the carbonation efficiency of the second treatment (as determined by CO2 absorption) was found to be similar to the value achieved for 80°C.
Claims
1. A mechanochemically carbonated slag having a carbonation temperature of 0.1-50 m 2 / g, preferably 0.5-50m 2 The invention has a specific surface area in the range of 200 Å / g and a D50 in the range of 0.1-50 μm, preferably 0.5-35 μm, most preferably 1-15 μm.
2. The mechanochemically carbonated slag of claim 1 having an amorphous content of at least 35 wt.% as determined by XRD and preferably one or two of the following features: D10 in the range of 0.005-10 μm, preferably 0.01-5 μm, most preferably 0.1-1.5 μm; • D90 in the range of 0.5-100 μm, preferably 1-60 μm, most preferably 1-50 μm.
3. The mechanochemically carbonated slag as claimed in claim 1 or 2, having an amorphous content of at least 50 wt.%, preferably at least 60 wt.%, more preferably at least 65 wt.% as determined by XRD.
4. The mechanochemically carbonated slag according to any preceding claim, having: 10 wt.% - 40 wt.% (based on the total weight of the mechanochemically carbonated slag) of SiO2; and Less than 90 wt.% (based on the total weight of the mechanochemically carbonated slag), preferably less than 80 wt.% (based on the total weight of the mechanochemically carbonated slag), more preferably less than 70 wt.% (based on the total weight of the mechanochemically carbonated slag), even more preferably less than 60 wt.% (based on the total weight of the mechanochemically carbonated slag) of metal oxides other than SiO2.
5. The mechanochemically carbonated slag as claimed in any preceding claim, having a strength activity index (SAI) at day 7 as determined according to ASTM C311 / C311M-22 of at least 85%, preferably at least 90%, more preferably at least 95% and a strength activity index (SAI) at day 28 as determined according to ASTM C311 / C311M-22 of at least 100%.
6. A method for producing mechanochemically carbonated slag, the method comprising the following steps: a) providing a raw material including a slag precursor; b) providing a gas comprising at least 0.5% by volume of CO2; c) introducing the raw material and the gas into a mechanical stirring unit; as well as d) subjecting the feedstock material to a mechanical stirring operation in the presence of the gas in the mechanical stirring unit.
7. The method of claim 6, wherein: The slag precursor has a thickness of less than 0.6 m 2 / g, preferably less than 0.5m 2 / g, more preferably less than 0.4m 2 / g of specific surface area of particulate material.
8. The method according to any one of claims 6 or 7, wherein: The gas provided in step (b) is a combustion flue gas, preferably a combustion flue gas from the combustion of fossil fuels, the combustion of wood pellets, the combustion of biomass or the combustion of municipal waste.
9. The method according to any one of claims 6 to 8, wherein: This step (d) is carried out as follows: at a pressure of less than 10000 kPa, preferably less than 5000 kPa, more preferably less than 2500 kPa and most preferably less than 1000 kPa; and - At a temperature of less than 100°C, preferably less than 80°C.
10. The method of claim 9, wherein: Step (d) is carried out at a temperature in the range of 30°C-50°C, and wherein the moisture content of the solid feedstock is at least 10 wt.%.
11. The method according to any one of claims 6 to 10, wherein: The feedstock provided in step (a) is a solid feedstock having a moisture content of less than 30 wt.% (based on the total weight of the solid feedstock), preferably less than 20 wt.%, more preferably less than 15 wt.%.
12. The method according to any one of claims 6 to 11, wherein: Carbonation, size reduction and / or surface area increase are achieved during step (d) such that the process has one, two, three or all four, preferably all four, of the following characteristics: the ratio of the CO2 content of the mechanochemically carbonated slag obtained in step (d) to the CO2 content of the slag precursor of step (a) is at least 1.5:1, preferably at least 2:1, more preferably at least 2.2:1, wherein the CO2 content is determined as the mass loss above 450°C measured by TGA using a temperature trace wherein the temperature is increased from room temperature to 800°C at a rate of 10°C / min; The ratio of the D50 of the mechanochemically carbonated slag obtained in step (d) to the D50 of the slag precursor of step (a) is less than 0.9:1, preferably less than 0.75:1, more preferably less than 0.6:1; The ratio of the specific surface area of the mechanochemically carbonated slag to the specific surface area of the slag precursor is at least 1.2:1, preferably at least 1.4:1, more preferably at least 1.6:1; The absolute difference between the amorphous content of the mechanochemically carbonated slag (expressed as % based on the total weight) and the amorphous content of the slag precursor (expressed as % based on the total weight) is at least 20 percentage points, preferably at least 30 percentage points, more preferably at least 35 percentage points.
13. The method according to any one of claims 6 to 12, wherein: The slag precursor is blast furnace (BF) slag, air cooled blast furnace (ACBF) slag, granulated blast furnace (GBF) slag, basic oxygen furnace (BOF) slag, ladle furnace basic slag (LS) or electric arc furnace (EAF) slag, preferably granulated blast furnace (GBF) slag or basic oxygen furnace (BOF) slag.
14. The method according to any one of claims 6 to 13, wherein: The slag obtained in step (d) has A strength activity index SAI of at least 85%, preferably at least 90%, more preferably at least 95% at day 7 as determined in accordance with ASTM C311 / C311M-22 and a strength activity index SAI of at least 100% at day 28 as determined in accordance with ASTM C311 / C311M-22; and / or • Water requirement of less than 94%, preferably less than 93%.
15. Mechanochemically carbonated slag obtainable by the method according to any one of claims 6 to 14.
16. A composition comprising the mechanochemically carbonated slag as claimed in any one of claims 1 to 5 or 15 and an additional material selected from the group consisting of asphalt, cement, geopolymers, polymers and combinations thereof, preferably cement, more preferably Portland cement.
17. A method for preparing concrete or mortar, the method comprising the following steps: (i) providing the mechanochemically carbonated slag as claimed in any one of claims 1 to 5 or 15 and a further material selected from the group consisting of asphalt, cement, geopolymers and combinations thereof, optionally in the form of the composition as described herein, wherein the further material is selected from the group consisting of asphalt, cement, geopolymers and combinations thereof; (ii) providing construction aggregates; (iii) contacting, preferably mixing, the mechanochemically carbonated slag of step (i) and the further material with the construction aggregate of step (ii) and optionally water.
18. Use of the mechanochemically carbonated slag according to any one of claims 1 to 5 or 15: as a filler, preferably as a filler in a material selected from the group consisting of asphalt, cement, mortar, geopolymers, polymers and combinations thereof; As a partial replacement for asphalt, geopolymer or cement in concrete or mortar; Increase the compressive strength of concrete or mortar; Improve the durability of concrete or mortar; Improve the durability of concrete or mortar by reducing chloride permeability and / or porosity; Improve the strength activity index of concrete or mortar; and / or Reduce the water demand of concrete or mortar, Preferably, · Simultaneously improve the strength activity index of concrete and reduce the water demand of concrete; or · Simultaneously improve the strength activity index of the mortar and reduce the water demand of the mortar.
Citation Information
Patent Citations
Production of a mainly carbonate bonded article by carbonation of alkaline materials
US8709151B2